2021
DOI: 10.3390/v13091825
|View full text |Cite
|
Sign up to set email alerts
|

Hypericin Inhibit Alpha-Coronavirus Replication by Targeting 3CL Protease

Abstract: The porcine epidemic diarrhea virus (PEDV) is an Alphacoronavirus (α-CoV) that causes high mortality in infected piglets, resulting in serious economic losses in the farming industry. Hypericin is a dianthrone compound that has been shown as an antiviral activity on several viruses. Here, we first evaluated the antiviral effect of hypericin in PEDV and found the viral replication and egression were significantly reduced with hypericin post-treatment. As hypericin has been shown in SARS-CoV-2 that it is bound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Although hypericin inhibits human immunodeficiency virus (HIV) in vitro and in vivo [ 38 , 39 ], a clinical trial revealed phytotoxicity of orally administered hypericin (0.5 mg/kg daily) without antiretroviral activity in a limited number of patients [ 40 ]. Moreover, hypericin inhibits the replication of α-coronaviruses (PEDV and TGEV) through the inhibition of M pro [ 41 ]. Hypericin inhibits M pro of SARS-CoV-2 with a CC 50 value of 63.6 µM [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hypericin inhibits human immunodeficiency virus (HIV) in vitro and in vivo [ 38 , 39 ], a clinical trial revealed phytotoxicity of orally administered hypericin (0.5 mg/kg daily) without antiretroviral activity in a limited number of patients [ 40 ]. Moreover, hypericin inhibits the replication of α-coronaviruses (PEDV and TGEV) through the inhibition of M pro [ 41 ]. Hypericin inhibits M pro of SARS-CoV-2 with a CC 50 value of 63.6 µM [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rest of ORF-1ab encodes nine accessory proteins and four structural proteins, i.e., spike (S), envelope (E), membrane (M), and nucleocapsid (N) [11,12]. The coronavirus main protease (M pro , also termed 3CL pro ) is a cysteine protease with cysteine 145 and histidine 41 in its active site [10]. Its structure is composed of two monomers, and each of them consists of three domains.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports on potential antiviral activities of the extract or its active ingredients, such as the naphtodianthrone hypericin, were published. In these studies, these antiviral activities were shown against herpes simplex virus type 1 [ 22 ], human cytomegalovirus [ 23 ], hepatitis B virus [ 24 ], influenza A virus [ 25 , 26 ], human immunodeficiency virus type 1 [ 27 ], and animal viruses [ 28 , 29 ], including the infectious bronchitis virus and the porcine epidemic diarrhea virus, as gamma- and alpha- coronaviruses, respectively [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are some compounds such as salinomycin ( Yuan et al, 2021 ), homoharringtonine ( Dong et al, 2018 ), and A77 1726 ( Li X. et al, 2020 ) preventing PEDV proliferation by affecting the host defense system. Many compounds inhibit PEDV replication by targeting PEDV 3CLpro, such as tomatidine ( Wang et al, 2020 ), hypericin ( Zhang Y et al, 2021 ), quercetin ( Li Z. et al, 2020 ), and GC376 ( Ye et al, 2020 ). PEDV RdRp also can be the target of antiviral drugs ( Xie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral drug molnupiravir for the treatment of mild-to-moderate COVID-19 in adults with at least one risk factor for severe illness has been authorized in UK since November 2021 ( Mahase, 2021a ). It has been reported that certain small molecules inhibit PEDV proliferation, but commercial drugs have not been developed yet ( Wang et al, 2020 ; Huan et al, 2021 ; Zhang Y et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%